Кажани України та їхні дослідники: 20 років активності та основні віхи - Загороднюк, І. (Theriologia Ukrainica, 2018)
Огляд росту й розвитку в Україні хіроптерологічних рухів та досліджень, пов’язаних з вивченням фауни, стану популяцій, задач охорони кажанів та просвіти громадян у питаннях охорони популяцій кажанів у природних і антропогенізованих місцезнаходженнях. Ці процеси розглянуто у розрізі чотирьох періодів розвитку: період 1: початки і перші інтенсиви (1995–2003), період 2: дослідницькі екстенсиви (2003–2009), період 3: червоні книги та урбістика (2010–2017), період 4: перспективи (подальше). Наведено огляд найважливіших видань монографічного плану, оглядів, тематичних збірників наукових праць, визначників, дисертацій. An overview of the growth and development of chiropterological movements in Ukraine and of research devoted to the study of fauna, status of populations, and problems of bat conservation, as well as the education of citizens in the protection of bat populations in natural and anthropogenic habitats. These processes are considered in the context of four developmental periods: period 1: beginnings and the first intensities (1995–2003), period 2: research extensions (2003–2009), period 3: “red” books and urban studies (2010–2017), period 4: perspectives (continued). An overview of the most important monographic editions, reviews, thematic collections of scientific works, field keys, and dissertations is given.